Cover Picture: Importance of the 6′‐Hydroxy Group and Its Configuration for Apramycin Activity (ChemMedChem 9/2014). Issue 9 (September 2014) - Mandhapati, Appi Reddy; Shcherbakov, Dimitri; Duscha, Stefan; Vasella, Andrea; Böttger, Erik C.; Crich, David
<x xml:space="preserve">Abstract</x> The front cover picture shows the atypical aminoglycoside antibiotic apramycin superimposed on helix 44 of bacterial (left), mitochondrial (center), and cytoplasmic (right) ribosomal RNA. Apramycin binding to the universally conserved decoding A site of the bacterial rRNA (cyan) is the origin of its antibacterial activity against a broad spectrum of Gram‐negative and Gram‐positive organisms including Pseudomonas aeruginosa. Sequence differences in the mitochondrial and cytoplasmic decoding A sites, in red, disrupt apramycin binding and confer on it a useful selectivity and lack of toxicity. The research presented in this paper reveals the axial 6′‐hydroxy group of apramycin (magenta) to be crucial for binding. For more details, see the Full Paper by Andrea Vasella, Erik C. Böttger, David Crich et al. on p. 2074 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>